2001
DOI: 10.1111/1468-2311.00206
|View full text |Cite
|
Sign up to set email alerts
|

The Performance of Volunteer Appropriate Adults: A Survey of Call Outs

Abstract: The 'appropriate adult' is intended to safeguard the interests of the young suspect in the police interview. This article discusses the criticisms of social workers' and parents' performance of the role and then considers the findings from a survey that explores volunteers' performance. The findings suggest that, when the volunteers surveyed contributed in the interview, they fulfilled the role as intended. This article also examines the implications of employing the survey method as a means of data collection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 8 publications
1
16
0
Order By: Relevance
“…Despite the importance of such a role, appropriate adults have received little attention in the psychological literature since the role was first created (Pierpoint, ). Research to date has found appropriate adults to be “passive” in their role (Evans, ; Pierpoint, ), which is of concern given the risk of miscarriages of justice. Furthermore, the custodial environment can exacerbate existing mental health problems and impede the suspect's ability to comprehend the judicial process.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the importance of such a role, appropriate adults have received little attention in the psychological literature since the role was first created (Pierpoint, ). Research to date has found appropriate adults to be “passive” in their role (Evans, ; Pierpoint, ), which is of concern given the risk of miscarriages of justice. Furthermore, the custodial environment can exacerbate existing mental health problems and impede the suspect's ability to comprehend the judicial process.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, relatives may be ill‐prepared, unsupportive, inactive, combative, or too emotionally involved (Evans ; Evans and Puech ; Littlechild ; Pierpoint ; Quinn and Jackson ). Relatives may, however, be preferred in the interests of expediency and cost‐effectiveness (Pearse ; Pierpoint ). Volunteers are also relatively costless but may be unrepresentative in terms of ethnicity, age, gender, etc., or may be unavailable when called upon.…”
Section: The Appropriate Adult Safeguard: Core Dimensions and Key Chamentioning
confidence: 99%
“…Hodgson 1997, White 2002, volunteer appropriate adults (e.g. Pierpoint 2001Pierpoint , 2006aPierpoint , 2008 and paid appropriate adults could remain, particularly as the 'adequate training' referred to in the proposals (listed in Figure 1) is not part of a national programme for all types of appropriate adult.…”
Section: Journal Of Social Welfare and Family Law 147mentioning
confidence: 99%
“…Moreover, there is a risk that, by layering on additional welfare functions, functions such as observing whether the interview is being conducted properly and fairly become diluted or lost, as in the Scottish scheme. Admittedly, the capacity of appropriate adults to complete this function is questionable (Irving and McKenzie 1989, Brown et al 1992, Thomas 1995, Pierpoint 1999, 2000a, 2000b, 2001, Brookman and Pierpoint 2002, 2003. However, it is arguable that it should be a specific individual's responsibility to guard against false confessions and ensure due process and the presumption of innocence are respected.…”
Section: H Pierpoint 150mentioning
confidence: 99%